QT dispersion in patients with cystic fibrosis [Kistik fibrozisli hastalarda QT dispersiyonu] - (:unkn) unknown (My University, 2004)
Cystic fibrosis is a common ion channel disease. Chronic pulmonary disease may lead to lethal complications including cor pulmonale. Several factors may be effective in arrhythmogenesis in these patients, which can include hypoxemia, hypercapnia, cor pulmonale, right ventricular dilatation, and sympathomimetic drugs. Increased QT dispersion (QTd) is an indicator of heterogeneous ventricular repolarization and is useful for prediction of lehal arrhythmia. We evaluated the electrocardiograms of 22 cystic fibrosis patients (mean age ± SD, 11.89 ± 5.46 years) and 22 healthy controls (mean age ± SD, 11.81 ± 6.99 years) for QT dispersion. QT dispersion and corrected QT dispersion (QTcd) were significantly increased in patients with cystic fibrosis compared to the control group. QTd were 56 ± 15 msec and 34 ± 12 msec respectively (p<0.0001). QTcd were 63 ± 12 msec and 44 ± 15 msec respectively (p<0.0001). In conclusion, ventricular repolarization is more heterogeneous in patients with cystic fibrosis compared to healthy children and this may be related to the increased risk of ventricular arrhythmia.
Keywords: Arrhythmia; Cystic fibrosis; Ion channel disease; QT dispersion